Integrin-Mediated Adhesion and Chemoresistance of Acute Lymphoblastic Leukemia Cells Residing in the Bone Marrow or the Central Nervous System - Scharff, Bibi Fatima Syed Shah; Modvig, Signe; Marquart, Hanne Vibeke; Christensen, Claus (Frontiers in Oncology, 2020)
Acute Lymphoblastic Leukemia (ALL) is the most common cancer in childhood. Despite a significantly improved prognosis over the last decade with a 5-years survival rate of 90%, treatment-related morbidity remains substantial and relapse occurs in 10–15% of patients (1). The most common site of relapse is the bone marrow, but early colonization and subsequent reoccurrence of the disease in the central nervous system (CNS) also occurs. Integrins are a family of cell surface molecules with a longstanding history in cancer cell adherence, migration and metastasis. In chronic lymphoblastic leukemia (CLL), the VLA-4 integrin has been acknowledged as a prognostic marker and mounting evidence indicates that this and other integrins may also play a role in acute leukemia, including ALL. Importantly, integrins engage in anti-apoptotic signaling when binding extracellular molecules that are enriched in the bone marrow and CNS microenvironments. Here, we review the current evidence for a role of integrins in the adherence of ALL cells within the bone marrow and their colonization of the CNS, with particular emphasis on mechanisms adding to cancer cell survival and chemoresistance.